HUBUNGAN GAYA KEPEMIMPINAN KEPALA SEKOLAH DENGAN KINERJA GURU DI SMK NEGERI 2 PARIAMAN - Frimaiyulis (Jurnal Bahana Manajemen Pendidikan, 2013)
This research about principal leadership style and teacher performance, also to see the relationship between the two variables. Population are 95 teachers and 48 samples using proportional stratified random sampling technique. This research instrument is a questionnaire in the form of a Likert scale, a score of variable principal leadership style 0.739 and teacher performance 0.812 that means instrument is reliable. Data were analyzed using product moment correlation, get rscore = 0.37> = 0.284 believed rtabel standard 95%. Research has come to the conclusion the relationship between principal leadership style with the performance of teachers in SMK 2 Pariaman. Key word: gaya kepemimpinan dan kinerja